The Scope of Pathogenic ABCA4 Mutations Targetable by CRISPR DNA Base Editing Systems—A Systematic Review - Piotter, Elena; McClements, Michelle E.; MacLaren, Robert E. (Frontiers in Genetics, 2022)
Stargardt macular dystrophy (STGD1) is the most common form of inherited childhood blindness worldwide and for which no current treatments exist. It is an autosomal recessive disease caused by mutations in ABCA4. To date, a variety of gene supplementation approaches have been tested to create a therapy, with some reaching clinical trials. New technologies, such as CRISPR-Cas based editing systems, provide an exciting frontier for addressing genetic disease by allowing targeted DNA or RNA base editing of pathogenic mutations. ABCA4 has ~1200 known pathogenic mutations, of which ~63% are transition mutations amenable to this editing technology. In this report, we screened the known ‘pathogenic’ and ‘likely pathogenic’ mutations in ABCA4 from available data in gnomAD, Leiden Open Variation Database (LOVD), and ClinVar for potential PAM sites of relevant base editors, including Streptococcus pyogenes Cas (SpCas), Staphylococcus aureus Cas (SaCas), and the KKH variant of SaCas (Sa-KKH). Overall, of the mutations screened, 53% (ClinVar), 71% (LOVD), and 71% (gnomAD), were editable, pathogenic transition mutations, of which 35-47% had ‘ideal’ PAM sites. Of these mutations, 16-20% occur within a range of multiple PAM sites, enabling a variety of editing strategies. Further, in relevant patient data looking at three cohorts from Germany, Denmark, and China, we find that 44-76% of patients, depending on the presence of complex alleles, have at least one transition mutation with a nearby SaCas, SpCas, or Sa-KKH PAM site, which would allow for potential DNA base editing as a treatment strategy. Given the complexity of the genetic landscape of Stargardt, these findings provide a clearer understanding of the potential for DNA base editing approaches to be applied as ABCA4 gene therapy strategies.